Telecommunications networks and public health responses during the COVID-19 pandemic: Evidence from a large national network operator in Canada - Joe Rowsell; Anthony Hertanto; Anand Mathur (International Telecommunications Society (ITS), 2021)
The COVID-19 pandemic has demonstrated the fundamental importance of telecommunications networks. This paper utilizes data from a large North American network operator to examine the role of telecom networks in enabling public health and economic responses to the pandemic. During the pandemic, data usage grew significantly, with growth in wireline data use outstripping growth in wireless data use, 53% to 27%, between March and December 2020. Yet, even at pre-pandemic levels, data use is growing exponentially, doubling every 1.3 years between 2017 and 2020. This paper also considers three examples of public health and economic responses enabled by telecom networks: staying at home, adopting telemedicine, and teleworking. First, based on de-identified data on customer movement and location, this paper estimates that compliance with stay-at-home orders was about 20% lower in the 2nd wave than during the 1st wave, despite much cases counts, suggesting that Canadians suffered from isolation fatigue. Across Canada's six largest cities, controlling for population and GDP per capita, a 1% decrease in compliance is associated with an additional 700 COVID-19 infections. Second, based on data on two telemedicine apps, this paper highlights the potential for the rapid adoption of telemedicine. At the start of the pandemic, adoption of these apps doubled and then was sustained throughout 2020, with usage patterns reflecting digital divides in age and gender. Third, Canada's teleworking rate changed in lockstep with COVID-19 cases, even while the unemployment rate remained constant, suggesting that employers are adopting teleworking as a flexible way to adapt to evolving public health conditions and restrictions without resorting to layoffs. When viewed against this backdrop, telecommunication policy can support public health and social outcomes, in addition to economic outcomes.
Keywords: 330